Predictable Movements in Yen/DM Exchange Rates - Kong, Janet (Washington, D.C. : International Monetary Fund, 2000)
This paper examines the relevance of PPP, the adjustment channel of real exchange rate and the predictability of the movement in nominal exchange rate by studying the behavior of yen/DM exchange rate, using cointegration method. Results support PPP and find that the real exchange rate is mean-reverting. The change in the nominal exchange rate exhibits significant auto-regressive property. These findings imply that movements in the nominal yen/DM exchange rate is actually predictable. The error-correction model and a simple first order autoregressive model both outperform the random walk model in out-of-sample forecasting.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet